The influence of the North Atlantic Oscillation and El Niño–Southern Oscillation on mean and extreme values of column ozone over the United States ... - Petropavlovskikh, I.; Evans, R.; McConville, G.; Manney, G. L.; Rieder, Harald (Columbia University, 2015)
Continuous measurements of total ozone (by Dobson spectrophotometers) across the contiguous United States began in the early 1960s. Here, we analyze temporal and spatial variability and trends in total ozone from the five US sites with long-term records. While similar long-term ozone changes are detected at all five sites, we find differences in the patterns of ozone variability on shorter timescales. In addition to standard evaluation techniques, STL-decomposition methods (Seasonal Trend decomposition of time series based on LOESS (LOcally wEighted Scatterplot Smoothing)) are used to address temporal variability and "fingerprints" of dynamical features in the Dobson data. Methods from statistical extreme value theory (EVT) are used to characterize days with high and low total ozone (termed EHOs and ELOs, respectively) at each station and to analyze temporal changes in the frequency of ozone extremes and their relationship to dynamical features such as the North Atlantic Oscillation (NAO) and El ...